Diversity, Nest Preferences, and Forage Plants of Stingless Bees (Hymenoptera: Apidae: Meliponini) from West Halmahera, North Moluccas, Indonesia - Hearty Salatnaya; A M Fuah; M S Engel; Cece Sumantri; Widiatmaka Widiatmaka; S Kahono (Jurnal Ilmu Ternak dan Veteriner, 2021)
Survey of stingless bee diversity, nesting preferences, and forage plants was conducted in West Halmahera across 134 collection sites. This research was aimed to determine species diversity, nesting preference and habitat, and dominant forage plants. There were three species found, the most common species being Tetragonula clypearis (Friese), followed by T. sapiens (Cockerell), and last T. biroi (Friese). Based on the morphology characters of each species, the key identification was provided. The most colonies were found in public houses (80.39%), followed by plantations (13.73%), and the community forest (5.88%), respectively.Most colonies nested in stone cavities, parts of the houses, wooden materials, tree trunks, logs, tree roots, bamboo, and sometimes iron cavities. The forage plants consist of forage plantation, crops, fruits, vegetables, ornamental flowers, wild plants and shrubs. The three species found were new record in West Halmahera. Bees lived in various hollow places that were safe for their colony. Bees made use of a variety of flowering plants and secrete resins around the nest site.